2018
DOI: 10.9778/cmajo.20180046
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the use of prenatal testing services for fetal aneuploidy in Ontario: a descriptive study

Abstract: Background: In 2014, Ontario augmented its publicly funded multiple-marker screening program for prenatal aneuploidy by incorporating cell-free fetal DNA (cffDNA) analysis for high-risk pregnancies. We assessed trends in the use of multiple-marker screening, cffDNA screening and prenatal diagnostic testing before and after implementation of public funding. Methods: We conducted a descriptive study based on data from the Better Outcomes Registry & Network (BORN) Ontario. The study population included all pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Studies have shown that when fetal aneuploidy screening is reimbursed, utilization increases significantly 19,24 . A Canadian survey study showed that a majority of pregnant women (66.4%) agreed that reimbursement of NIPT would greatly impact their decision to choose the test 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when fetal aneuploidy screening is reimbursed, utilization increases significantly 19,24 . A Canadian survey study showed that a majority of pregnant women (66.4%) agreed that reimbursement of NIPT would greatly impact their decision to choose the test 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Germanyā€™s publicly funded health insurance system plans to cover NIPT for trisomies 21, 13, and 18 for particular pregnancies with increased need of surveillance and pregnancies with special risks. Introduction of nationwide health coverage for NIPT has been shown to result in a considerable increase in update of this type of prenatal screening for women with increased risk of fetal aneuploidy [ 43 , 44 ]. It is important that patients are informed that NIPT is not a diagnostic test, and that high-risk NIPT calls should be confirmed by invasive diagnostic procedures such as CVS or amniocentesis.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). So far the uptake of NIPT in the Netherlands is moderate, however, it is expected to significantly increase if it could be reimbursed similar to screening by ultrasound [ 11 , 12 ]. In Dutch settings the expectation is that after subsequent FAS, about 0.2ā€“0.3% of patients with normal NIPT results will show abnormal FAS outcome [ 6 ].…”
Section: Genotyping First or Phenotyping First?mentioning
confidence: 99%